ChemInform Abstract: Ru(II)‐Catalyzed C—H Activation: Ketone‐Directed Novel 1, 4‐Addition of ortho C—H Bond to Maleimides. Issue 9 (February 2016) - Bettadapur, Kiran R.; Lanke, Veeranjaneyulu; Prabhu, Kandikere Ramaiah
Abstract: Maleimides add to the ortho‐position of aryl ketones to furnish regioselectively the o‐(succinimid‐3‐yl)aryl ketones in good to high yields.